Description of Increasing the Number of Research and Publication of Lecturers at the Indonesian Christian University, East Jakarta - Mesta Limbong; Faradiba F; Nelius Harefa; Jitu Halomoan Lumbantoruan (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The purpose of the study was to determine the readiness and difficulty of photographing and to improve research and publications of lecturers in Jakarta through lecturers at the Indonesian Christian University (UKI). Research is one of the indicators of the tridarma that must be carried out by lecturers throughout Indonesia, including lecturers at UKI. One proof of its performance is its publication in international and nationally reputable journals. Because research has a maximum dual effect and contributes to policy making in institutions. Allegedly there was a time when there were absolutely no lecturers who ran the administration of Academic Position. To become a superior university, one of the determining indicators is evidenced by the number of lecturers with the highest Academic Position. Data were obtained from secondary data and primary data as well as filling out questionnaires addressed to lecturers in the UKI environment. Data were collected from 102 respondents from 33 study programs. The results, which include lecturer research data and observations for the last four years from 2017 - 2020, show an increase in the number of publications in reputable and local international and national journals, although the results are comparable between the number of lecturers and publications. The backwardness of the publication of scientific journals of national and international repute can only be achieved if each lecturer conducts a scientific study and is published in accordance with the UKI Research and Community Service (LPPM) program, that each lecturer has the opportunity to conduct research twice a year, both independent research and research research group.